Effect of chicken eggshell on the flame‐retardant and smoke suppression properties of an epoxy‐based traditional APP‐PER‐MEL system. Issue 7 (28th October 2018) - Xu, Zhisheng; Chu, Zhiyong; Yan, Long; Chen, Hongguang; Jia, Hongyu; Tang, Wufei
Abstract : An eco‐friendly bio‐filler was prepared by reusing of chicken eggshell (CES), and well characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscope (SEM)‐energy dispersive X‐ray spectroscopy (EDS), X‐ray fluorescence spectrometry (XRF), and thermo‐gravimetric (TG) analysis. The influence of CES on the thermal stability, flame‐retardant, and smoke suppression properties of epoxy‐based traditional intumescent system was investigated by limited oxygen index (LOI), UL 94 test, cone calorimeter test, and TG analysis. The results shows that the incorporation of CES improves the LOI value of the samples, and IFR‐3 with 37 wt% intumescent flame retardant (IFR) and 3 wt% CES exhibits the maximum LOI value of 31.5%. The results from cone calorimeter and smoke density tests reveal that the addition of CES greatly decreases the heat release and smoke production of the samples concomitant with an increase in the residual weight, which is ascribed to the formation of a more compact, thermally stable, and intumescent char against heat and mass transfer during burning. The synergistic effect on fire performance between CES and IFR depends on the content of CES, and an excessive content of CES diminishes this synergistic effect. The TG analysis shows that the intumescent system containing CES exhibits high thermal stability and char‐forming ability. Overall, CES can serve as an environmentally friendly bio‐filler and a promising synergist for intumescent systems. POLYM. COMPOS., 40:2712–2723, 2019. © 2018 Society of Plastics Engineers